MUNICIPAL LIBRARIES AND NEW TECHNOLOGIES - NIKTA, MARINA; Karydis, Christos (Qualitative and Quantitative Methods in Libraries, 2022)
The constantly changing conditions in today's society, with the advances of information and communication technology, have not left the Public Libraries unaffected. On the contrary, the introduction of new technology in them imposed changes in all areas of their activity in order to be able to meet the modern demands of users, and signaled their entry into a new era, where their position was in fact more upgraded as channels of Knowledge and information.Rapid developments in the production, distribution, organization, and utilization of the information provided by the library have led, almost certainly, not only to new tools and ways of carrying out the information task, but, above all, to the creation of a new and completely different perceptions and attitudes.